Tolerance of an acute warming challenge declines with body mass in Nile tilapia: evidence of a link to capacity for oxygen uptake - Blasco, Felipe R. [UNESP]; Taylor, Edwin W.; Leite, Cleo A C; Monteiro, Diana A.; Rantin, F Tadeu; McKenzie, David J. (The Company of Biologists, 2022)
It has been proposed that larger individuals within fish species may be more sensitive to global warming, as a result of limitations in their capacity to provide oxygen for aerobic metabolic activities. This could affect size distributions of populations in a warmer world but evidence is lacking. In Nile tilapia Oreochromis niloticus (n=18, mass range 21-313 g), capacity to provide oxygen for aerobic activities (aerobic scope) was independent of mass at an acclimation temperature of 26°C. Tolerance of acute warming, however, declined significantly with mass when evaluated as the critical temperature for fatigue from aerobic swimming (CTSmax). The CTSmax protocol challenges a fish to meet the oxygen demands of constant aerobic exercise while their demands for basal metabolism are accelerated by incremental warming, culminating in fatigue. CTSmax elicited pronounced increases in oxygen uptake in the tilapia but the maximum rates achieved prior to fatigue declined very significantly with mass. Mass-related variation in CTSmax and maximum oxygen uptake rates were positively correlated, which may indicate a causal relationship. When fish populations are faced with acute thermal stress, larger individuals may become constrained in their ability to perform aerobic activities at lower temperatures than smaller conspecifics. This could affect survival and fitness of larger fish in a future world with more frequent and extreme heatwaves, with consequences for population productivity.
Keywords: Exercise performance; Respiratory metabolism; Thermal tolerance